The Impact of Payments for Reforestation in the Mexican State Michoacán - Elsa Maria Cardona Santos; Daniel Kyalo Willy; Karin Holm-Müller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
As a means to adapt to climate change, the Mexican government grants, since 2003, payments as an incentive for landholders to conserve, maintain and increase the provision of environmental services through the promotion of a forestry strategy. This paper contributes to the literature with an empirical analysis of the impact of payments for reforestation in one of the states with the highest rates of deforestation, Michoac n. The impact is estimated by means of panel data regressions and propensity score matching. Our results suggest that the payments are not contributing to the overall reforestation in Michoac n because of the existence of leakage in areas that are not participating in the program. Our analysis underlines the challenges faced when implementing financial incentive based programs and provides policy makers with evidence for improving the design of such programs.
Keywords: Q23; C87; Q38; 330